Comparison of Effectiveness of Intrathecal Tramadol versus Intravenous Tramadol in Prevention of Post-Anesthesia Shivering in Patients Undergoing Lower Limb Orthopedic Surgeries under Subarachnoid Block: A Comparative Study: Intrathecal vs Intravenous Tramadol in Post-Anesthesia Shivering - Khalid, Sameen; Ahmad, Humaira; Khalid, Muhammad; Khalid, Maliha (Pakistan Journal of Health Sciences, 2025)
Shivering is a common spinal anesthetic side effect that occurs in 40–60% of people who have had subarachnoid block. Shivering is typified by spontaneous, involuntary, rhythmic fasciculation or skeletal muscular activation that resembles tremors. Hypothalamic thermoreceptors attempt to increase heat synthesis by shivering when they sense this drop in core body temperature due to peripheral heat redistribution. Objectives: To compare anti-shivering effects of intravenous versus intrathecal tramadol in patients receiving subarachnoid block for lower limb orthopedic operations. Methods: This Quasi-experimental study included 130 patients scheduled for elective orthopedic surgery under spinal anesthesia in the Operation Theater, Allied Hospital, Faisalabad. Patients were randomly divided into two groups: Group A (intrathecal tramadol with bupivacaine) and Group B (intravenous tramadol with intrathecal bupivacaine). The frequency of post-anesthesia shivering was recorded in both groups. Results: The mean ± SD of sensory and motor block duration in Group A was 331.72 ± 33.09 and 231.14 ± 11.22 minutes, respectively, while in Group B it was 228.12 ± 12.15 and 157.42 ± 10.02 minutes, respectively (p<0.001). Post-anesthesia shivering occurred in 9 (13.84%) patients in Group A and 23 (35.38%) patients in Group B (p<0.05). Conclusions: Post-anesthesia shivering was significantly higher in patients receiving intravenous tramadol (Group B) compared to those receiving intrathecal tramadol (Group A).